Formulation and Physical Properties Evaluation of Ethanol Extract of Tapak Liman Leaves (Elephantopus scaber L.) Gel Preparation - Pratiwi, Niken; Nisa, Khairun; Ariani Edityaningrum, Citra (Clinical and Pharmaceutical Sciences Journal, 2025)
Management of diabetic wounds is crucial to prevent severe complications including the potential of amputation. The conventional treatments often involve antibiotics as resistance frequently arises. Tapak liman (Elephantopus scaber L.) leaf extract, as an antibacterial agent, could be an alternative for treating diabetic wounds. For practical application, the extract is formulated into a gel. The objective of this study is to determine the concentration of the gelling agent HPMC and the humectant propylene glycol that can create the gel optimal formula, meeting the criteria for favorable physical properties. The study commences with the identification and phytochemical screening of tapak liman leaves extract. Subsequently, the extract was formulated in the forms of gels with concentrations of HPMC and propylene glycol. The evaluation included the testing of organoleptic, viscosity, pH, spreadability, and adhesiveness. Data is then subjected to analysis, beginning with normality tests followed by One-way ANOVA, in order to achieve the gel formula exhibiting the most favorable physical properties. This study reveal the following physical properties for F1, F2, and F3, respectively: pH values of 5.86 ± 0.257; 5.60 ± 0.068; and 5.53 ± 0.075, viscosities of 149.4233 ± 42.71002; 1,203.44 ± 154.1854; and 2,283.10 ± 530.2867 (cps), spreadability of 41.365 ± 0.47; 23.225 ± 0.64; and 18.805 ± 0.26 (g.cm/second), as well as adhesiveness of 1.59 ± 0.57; 2.08 ± 0.51; and 7.77 ± 1.14 (seconds). Based on the results above, it can be concluded that F3, with HPMC and propylene glycol concentrations of 3% and 14%, represents the optimal formula, demonstrating the best physical properties for a gel.